The effect of small-scale habitat features on groundfish density in deep-sea soft-bottom ecosystems. (March 2023) - Boulard, Marion; Lawton, Peter; Baker, Krista; Edinger, Evan
Abstract: In the deep-sea, cold-water corals (CWCs) and other structure-forming fauna locally increase habitat complexity and are host to many fish species. While many studies have focused on hard-bottom CWCs, very little is known about fish associations with soft-bottom CWC habitats. To understand the small-scale linkages between fish, benthic and non-bio-structural habitats in a soft-sediment deep-sea environment, we analysed remotely operated vehicle (ROV) survey videos and recorded the occurrence of fish, invertebrate habitat-forming species and substratum along transects, in the Laurentian Channel Marine Protected Area (MPA) in the Canadian Northwest Atlantic. Almost 13, 300 individual fish were recorded, of which all but 65 specimens were identified to family or lower taxonomic rank. The five numerically dominant fish taxa were Redfish ( Sebastes spp . ), Witch Flounder ( Glyptocephalus cynoglossus ), Marlin-Spike Grenadier ( Nezumia bairdii ), Longfin Hake ( Phycis chesteri ) and one Teleostei morphotype. Teleostei sp1 represents three fish genera (Sandlance ( Ammodytes spp.) and two Barracudinas ( Arctozenus sp. and Paralepis spp.)) morphologically difficult to differentiate on video footage. Multivariate analysis revealed four habitats based on epibenthic invertebrate densities and diversity. These were dominated by various combinations of sea anemones (Actiniaria), nephtheid soft coral, solitary cup corals (Scleractinia) and three taxa of sea pen ( Pennatula spp., Kophobelemnon sp. and Anthoptilum spp.). Univariate analyses performed on dominant fish densities revealed the local influence of hard-bottom substrates and the common influence of soft-sediment micro-features for three fish taxa. All fish densities were correlated with invertebrate density, negatively for Redfish and positively for all other taxa. Our models also predicted the association of four fish taxa with one to two benthic habitats within their preferred depth range. Our results suggest that small-scale habitat heterogeneity in a low relief soft-sediment environment, provided by both physical and biological structures, has a measurable species-specific influence on fish communities. This influence was weaker than typical fish-habitat relationships found in hard-bottom systems, suggesting fish-invertebrate relationships are not obligate. Additionally, we provided evidence that Redfish continue occupying sea pen habitats months after spawning. Our study supports the necessity to continue monitoring the MPA using in-situ video systems to understand the links between fish and habitats in the Laurentian Channel. Highlights: Evidence of taxon-specific influence of specific habitat biotic and abiotic features on fish density Evidence of taxon-specific influence of specific CWC taxa on fish density Results suggest a facultative relationship between fish and invertebrates in soft-bottom ecosystems. Evidence of occupation and multiple use of specific sea pen habitats by Redfish for months after spawning. ROV is an efficient tool for detecting in-situ small-scale associations of fish in their habitat.